The correlation between ejection fraction values and blood urea nitrogen levels and blood urea nitrogen/creatinine ratios in heart failure - Jaury, Daniel Francis; Mappangara, Idar; Rasyid, Haerani; Bakri, Syakib; Aman, Andi Makbul; Zainuddin, Andi Alfian (Acta Biomedica Atenei Parmensis, 2026)
Background: Heart failure is a condition with high mortality characterized by a decrease in the heart's ability to pump blood. Decreased EF can affect renal perfusion and trigger renal dysfunction, as reflected in increased BUN and altered BUN/Cr ratio. Therefore, the relationship between EF and these biochemical parameters is important to support clinical assessment in patients with heart failure. The purpose of this study was to determine the correlation between EF values and BUN levels and BUN/Cr ratio in patients with heart failure.Materials and Methods: An analytical observational study with a cross-sectional design involving 456 patients with heart failure at Wahidin Sudirohusodo Hospital, Makassar, Indonesia. EF values were obtained from echocardiography, and BUN and creatinine levels were measured through laboratory tests.Result: Patients with HFrEF showed significantly higher mean BUN levels compared to HFmrEF and HFpEF (55.08 ± 38.49 mg/dL vs. 50.87 ± 35.31 mg/dL vs. 37.78 ± 21.50 mg/dL, respectively; p < 0.001). HFrEF patients showed significantly higher mean BUN/Cr ratios compared to HFmrEF and HFpEF (48.94 ± 28.10 mg/dL vs. 45.56 ± 24.63 mg/dL vs. 41.25 ± 22.41 mg/dL, respectively; p = 0.04).Conclusion: Patients with heart failure with low ejection fraction (HFrEF) had the highest BUN levels and BUN/creatinine ratios compared to the HFmrEF and HFpEF groups. These findings confirm that renal dysfunction is more common in patients with low ejection fraction, and monitoring BUN parameters and BUN/creatinine ratios can be important indicators in assessing the severity of heart failure.